Clinical outcomes of patients undergoing cardiac surgery in a hospital in northwest of Rio Grande do Sul - Miquéias Bogado Kasctin dos Santos; Camila Rieffel Silveira; Maria Antonieta Pereira de Moraes; Emiliane Nogueira de Souza (Revista de Enfermagem da Universidade Federal de Santa Maria, 2016)
Aim: To analyze the clinical outcomes of patients undergoing cardiac surgery in a high complexity hospital. Method: Descriptive historical longitudinal study, in which records of patients undergoing cardiac surgery within the period of one year were analyzed. Results: Among the 137 patient records analyzed, CABG surgery was the most prevalent 85 (62%). The average length of stay in the ICU was 2.93 ± 4.53 days, and clinical / surgical units, was 3.77 ± 3.53 days. The most used drugs were the vasoactive ones. The most prevalent complications in the postoperative period were hypotension 50 (36.6%), bleeding 17 (12.4%) and hyperglycemia 10 (7.3%). The average time of the chest tube removal was 51h43min , the use of mechanical ventilation was 16:38min and of the endotracheal tube was 16:48min. Conclusion: The major clinical outcomes in post-cardiac surgery are related to the hemodynamic status of the patient